Analisis Tingkat Kepuasan Penumpang Terhadap Pelayanan Bus Trans Metro Deli Rute Medan Tuntungan – Lapangan Merdeka - Kamilia Azhaari Ginting; Hermansyah Hermansyah; Suranto Suranto (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
The development of technology requires humans to fulfill their daily needs to be more complex. Therefore, Kementrian Republik Indonesia provides Trans Metro Deli Transportation services with the Bus Rapid Transit (BRT) implementation program which has a mission to provide the best service which includes aspects of security, accuracy, regularity, convenience, speed, comfort and satisfaction for its users. The purpose of this study was to find out how the services provided were based on passenger ratings. This research was conducted by distributing questionnaires to 100 respondents. The questionnaire contains the five dimensions of Service Quality (tangible, reliability, responsiveness, empathy and assurance) using a Likert Scale technique. The method used to get the value of the gap between performance and expectations is gap analysis and to measure the level of passenger satisfaction is the analysis of the Customer Satisfaction Index (CSI). From the calculation results of the gap analysis, it shows that the service quality of the Trans Metro Deli Bus is all negative indicator variables starting from -0.10 on the B1 attribute to -0.77 on the A5 attribute, which means that all services provided to passengers are still below passenger expectations. However, based on the satisfaction index, the CSI value is in the range of 80% - 84%, namely 82.61%, which means that the overall quality of performance is still in the satisfied criteria. The conclusion of this study is that the company must continue to improve the quality of service in order to increase the level of passenger satisfaction.